An investigation of Relationship between Accounting and Economical Performance Measures with Market Value of Companies in Cement and Petrochimical Industries in Tehran Stock Exchange - Ahmad Pouyanfar; Farzin Rezaee; Shahla Safabakhsh (بررسی‌های حسابداری و حسابرسی, 2010)
The main measure for creating value in enterprises from the viewpoint of managerial accounting is the size and continuity of residual income, which measured in the form of economic value added. The problem in the use of economic value added measure in Tehran Stock Exchange is the number of low observations. This study employs pooled Bootstrap regression on the cross sectional data of 23 cement and petrochemical companies listed in the TSE over the period 1378 – 1387 to examine whether EVA® or the traditional accounting-based measures are associated more strongly with stock returns. Empirical results indicate that the relative information contents of the economic measures are greater than that of earnings.